The Christmas engines - Allcroft, Britt; Moraghan, Mark, 1963-; Stourton, Tom; Mantle, Clive; Awdry, W.; HIT Entertainment; Universal Studios Home Entertainment (Firm) (Universal City, CA Universal Studios Home Entertainment, 2014)
Thomas and his friends are in holly, jolly Christmas spirits, ready to be Santa's engine helpers. Percy brings holiday fun to Reg at the scrap yard, while Duncan tries to overcome his bah humbug attitude. Thomas clears the snowy tracks so Connor can race passengers home in time for the holiday. James causes confusion and delay helping Duck get unstuck, as an old friend returns to Sodor bringing Percy the perfect gift.
Last train for Christmas ; Long lost friend ; Duncan the humbug ; Duck in the water ; The perfect gift.
Title from container.
Originally aired as episodes of a television show in 2014.
Based on the Railway series by the Reverend W. Awdry.
Wide screen (1.78:1).
Bonus features: It's Christmas time sing-along music video; Guess who? puzzles.
Created by Britt Allcroft.
Keywords: Awdry, W. -- Film adaptations; Thomas, -- the Tank Engine (Fictitious character) -- Juvenile films; Santa Claus -- Juvenile drama; Imaginary places -- Juvenile drama; Railroad trains -- Juvenile drama; Friendship -- Juvenile drama; Thomas the Tank Engine (Fictitious character) -- Drama; Railroads -- Trains -- Drama; DVDs; DVD-Video discs; Videodiscs; Animated television programs -- Juvenile; Film adaptations -- Juvenile; Video recordings for the hearing impaired -- Juvenile; Drama; Children's films; Children's television programs; Christmas television programs; Juvenile works